The inner and outer compartments of mitochondria are sites of distinct cAMP/PKA signaling dynamics. - Lefkimmiatis, K; Leronni, D; Hofer, A (2013)
Cyclic AMP (cAMP)-dependent phosphorylation has been reported to exert biological effects in both the mitochondrial matrix and outer mitochondrial membrane (OMM). However, the kinetics, targets, and effectors of the cAMP cascade in these organellar domains remain largely undefined. Here we used sensitive FRET-based sensors to monitor cAMP and protein kinase A (PKA) activity in different mitochondrial compartments in real time. We found that cytosolic cAMP did not enter the matrix, except during mitochondrial permeability transition. Bicarbonate treatment (expected to activate matrix-bound soluble adenylyl cyclase) increased intramitochondrial cAMP, but along with membrane-permeant cAMP analogues, failed to induce measureable matrix PKA activity. In contrast, the OMM proved to be a domain of exceptionally persistent cAMP-dependent PKA activity. Although cAMP signaling events measured on the OMM mirrored those of the cytosol, PKA phosphorylation at the OMM endured longer as a consequence of diminished control by local phosphatases. Our findings demonstrate that mitochondria host segregated cAMP cascades with distinct functional and kinetic signatures.